Carcinoma in Situ of the Cervix - Wright, V. Cecil (1971)
Carcinoma in situ is not always cured (even though it could be) because of errors in morphological diagnosis and inadequate operative techniques. In the past we have been conditioned to accept the tissue biopsy diagnosis in preference to the cytological diagnosis. In many cases positive exfoliative cytology has not been explained by tissue biopsy, mainly because the technique of tissue sampling has been inadequate. Insufficient operative techniques have failed to remove sufficient vaginal vault adjacent to the cervix. Failure to recognize that these early lesions may spread to the vaginal vault has resulted in a recurrence to the vaginal apex, either as a carcinoma in situ or an early invasive carcinoma. Because of the multicentricity of carcinoma in situ, cancerization of the entire female genital tract may occur. It is therefore mandatory that all patients be followed up with cytology after any method of management.